2010
DOI: 10.1093/aob/mcq025
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiencies of spring barley grown under varying nitrogen conditions in the field and growth chamber

Abstract: Determining which trait(s) or gene(s) to target to improve barley NUE is important and can be facilitated using simplified growth approaches to help determine the NUE phenotype of various genotypes. The genotypes studied showed similar growth and NUE characteristics across field and growth-chamber tests demonstrating that simplified, low-variable growth environments can help pinpoint genetic targets for improving spring barley NUE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 28 publications
10
64
0
Order By: Relevance
“…To improve the nitrogen use efficiency it is necessary to improve both nitrogen utilization effi- Notes: Values within the row marked either with the same letter or without exponents are not statistically different at P < 0.05 ciency (NUtE) and nitrogen uptake efficiency (NUpE) (Beatty et al 2010). The CULTAN treatment, however, led solely to significantly increased nitrogen utilization efficiency which is insufficient to improve nitrogen use efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the nitrogen use efficiency it is necessary to improve both nitrogen utilization effi- Notes: Values within the row marked either with the same letter or without exponents are not statistically different at P < 0.05 ciency (NUtE) and nitrogen uptake efficiency (NUpE) (Beatty et al 2010). The CULTAN treatment, however, led solely to significantly increased nitrogen utilization efficiency which is insufficient to improve nitrogen use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The application of slow and controlled release fertilizers reduces environmental pollution in terms of hazardous gaseous emissions and water eutrophication (Azeem et al 2014) and simultaneously enhances nitrogen use efficiency (Ladha et al 2005) which is an important presupposition for the increased profit of production (Beatty et al 2010;Gaju et al 2011). However, the use of these fertilizers is substantially limited by their higher cost (Zebarth et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…So, split N application regimes result in considerable boost in NUE, production, and resultantly RUE by reducing losses and improving uptake [41]. It is a rising concern that most of the available or applied N is lost, thereby reducing NUE, which is just 29% for cereals in developing agrarian economies [55,56]. This research study was carried out to validate the influence of split N application on biomass accumulation, grain yields, and resource use efficiencies such as NUE and RUE for C 3 winter and C 4 summer cereals.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on genetic variation for NUE in various crops reported large interactions between genotype and N stress and other environmental conditions (Cabrera-Bosquet et al 2007, Anbessa et al 2009, Beatty et al 2010, Wei et al 2012, Chen et al 2013). The investigations of Bouchet et al (2014), using an oilseed rape mapping population are a good example of such studies in which they determined genomic regions (Quantitative Trait Loci (QTLs)) associated with yield and assessed their stability under contrasting nitrogen nutrition regimes.…”
Section: Screening Methodologies For Nuementioning
confidence: 99%
“…The definition of NUE applied in this study is the yield produced per unit of added N (Dresbøll and Thorup-Kristensen 2014). NUE is already an important target for breeding research in many crops such as wheat (Cabrera-Bosquet et al 2007), barley (Anbessa et al 2009, Beatty et al 2010, rice (Wei et al 2012, Chen et al 2013, and oilseed rape (Koeslin-Findeklee et al 2014).…”
Section: Introductionmentioning
confidence: 99%